2007
DOI: 10.4049/jimmunol.178.4.2448
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Phagocytosis of Influenza Virus-Infected, Apoptotic Cells by Neutrophils and Macrophages in Mice

Abstract: Influenza virus-infected cells undergo apoptosis and become susceptible to phagocytosis by macrophages in vitro, and this leads to the propagation of the virus being inhibited. We previously showed that inhibitors of phagocytosis increased the rate of mortality among influenza virus-infected mice. However, the mode of the phagocytosis of influenza virus-infected cells in vivo has not been investigated. We, in this study, assessed this issue by histochemically analyzing bronchoalveolar lavage cells and lung tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
238
4
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(252 citation statements)
references
References 43 publications
8
238
4
2
Order By: Relevance
“…The phagocytic capacity of mouse PEC macrophages is enhanced when they are cultured with IAVinfected epithelial cells [62]. Similarly, BAL macrophages from IAV-challenged mice contain engulfed apoptotic cells and AMs from IAV-infected mice show greater phagocytic capacity towards apoptotic thymocytes than AMs from uninfected mice [63,64]. Together, these data suggest that macrophages play a role in clearing dead infected epithelial cells during IAV infection.…”
Section: Iav Replication and Macrophage Phagocytosissupporting
confidence: 53%
See 1 more Smart Citation
“…The phagocytic capacity of mouse PEC macrophages is enhanced when they are cultured with IAVinfected epithelial cells [62]. Similarly, BAL macrophages from IAV-challenged mice contain engulfed apoptotic cells and AMs from IAV-infected mice show greater phagocytic capacity towards apoptotic thymocytes than AMs from uninfected mice [63,64]. Together, these data suggest that macrophages play a role in clearing dead infected epithelial cells during IAV infection.…”
Section: Iav Replication and Macrophage Phagocytosissupporting
confidence: 53%
“…Together, these data suggest that macrophages play a role in clearing dead infected epithelial cells during IAV infection. Phagocytosis of apoptotic epithelial cells is a protective host response, as increased phagocytic capacity correlates with lower IAV lung titres in mice and inhibition of phagocytosis during IAV infection in vivo enhances virus lethality [63,64].…”
Section: Iav Replication and Macrophage Phagocytosismentioning
confidence: 99%
“…Interestingly, the “bacterial‐sensing” TLRs (2 and 4) were also reported to be suppressed 27, 28. Downregulation of these TLRs may impair phagocyte recruitment and bacterial elimination, contributing to the risk of secondary infections 9, 30, 31, 32. We found no significant difference in TLR expression pattern or magnitude between A/H3N2 and A/H1N1pdm09 infections, unlike their adaptive immune responses 20.…”
Section: Discussionmentioning
confidence: 56%
“…Broadly, viral nucleic acids (dsRNA, ssRNA, CpG oligodeoxynucleotides) are detected by the endosomal TLRs (3, 7, 8, 9), whereas components of bacteria (peptidoglycans/lipoproteins, lipopolysaccharides) are detected by the cell surface TLRs (2, 4) 3, 4. Recent in vitro and in vivo studies on influenza pathogenesis have shown that TLR activation induces expression of type I interferons and pro‐inflammatory cytokines (e.g., IL‐6, TNF‐α), limiting viral replication and dissemination, mediating tissue inflammation, and link to adaptive immunity development 3, 7, 8, 9, 10, 11, 123, 7, 10, 13.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils adhere to virus-infected epithelial cells (67) and virions (68) to mediate phagocytosis and/or stimulate activation signals, including production of reactive oxygen species. Neutrophils exposed to influenza virus undergo activation of the respiratory burst, followed by depression of cell function when subsequently exposed to secondary stimuli (69), although innate defense proteins of the collectin family have been shown to protect neutrophils from these depressive effects (70).…”
Section: Discussionmentioning
confidence: 99%